2023
DOI: 10.3389/fmed.2023.1100211
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of mitochondrial oxidative stress-related peptides MOTS-c and Romo1 in stable COPD: A cross-sectional study

Abstract: BackgroundMOTS-c and Romo1 are mitochondrial peptides that are modulated by oxidative stress. No previous studies have explored circulating levels of MOTS-c in patients with chronic obstructive pulmonary disease (COPD).MethodsWe enrolled 142 patients with stable COPD and 47 smokers with normal lung function in an observational cross-sectional study. We assessed serum levels of both MOTS-c and Romo1 and associated these findings with clinical characteristics of COPD.ResultsCompared with smokers with normal lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…ROC curve analysis was performed in MEDCALC version 11.6.1.0 (MedCalc Software, Mariakerke, Belgium). Evaluation of HN, GDF15, MOTS-c, FGF-21 and Romo1 as dichotomized variables, with a cut-off at the median, resulted in the best discriminative power, as reported in our previous studies 22 , 23 and other similar studies. 24 , 28 We evaluated cross-sectional associations with high versus low circulating mitochondrial peptides through logistic regression with re-hospitalization as the outcome variable.…”
Section: Methodssupporting
confidence: 82%
See 3 more Smart Citations
“…ROC curve analysis was performed in MEDCALC version 11.6.1.0 (MedCalc Software, Mariakerke, Belgium). Evaluation of HN, GDF15, MOTS-c, FGF-21 and Romo1 as dichotomized variables, with a cut-off at the median, resulted in the best discriminative power, as reported in our previous studies 22 , 23 and other similar studies. 24 , 28 We evaluated cross-sectional associations with high versus low circulating mitochondrial peptides through logistic regression with re-hospitalization as the outcome variable.…”
Section: Methodssupporting
confidence: 82%
“…Previously, we demonstrated that MOTS-c levels are diminished in SCOPD. 23 Here, we showed that these levels are even lower in ECOPD than SCOPD. Furthermore, GDF15 and MOTS-c levels were negatively correlated, indicating that GDF15 and MOTS-c show opposite responses.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations